2014
DOI: 10.1371/journal.pone.0092375
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Strains of Acanthamoeba Are Recognized by TLR4 and Initiated Inflammatory Responses in the Cornea

Abstract: Free-living amoebae of the Acanthamoeba species are the causative agent of Acanthamoeba keratitis (AK), a sight-threatening corneal infection that causes severe pain and a characteristic ring-shaped corneal infiltrate. Innate immune responses play an important role in resistance against AK. The aim of this study is to determine if Toll-like receptors (TLRs) on corneal epithelial cells are activated by Acanthamoeba, leading to initiation of inflammatory responses in the cornea. Human corneal epithelial (HCE) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…172,173 Acanthamoeba is recognised by TLR4, which initiates the MyD88/NF-kB pathway and also the MAPK/ERK pathway, leading to release of proinflammatory and chemotactic mediators such as IL-8, CXCL2, TNF-α, and IFN-β. 174,175 Macrophage activation in the presence of antiAcanthamoeba antibody and IFN-γ has been shown to demonstrate trophozoite killing activity. 167,176 Macrophages are thought to be a crucial mediator in early infection: depletion of macrophages in a Chinese hamster model of Acanthamoeba keratitis produced a notable worsening of disease.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…172,173 Acanthamoeba is recognised by TLR4, which initiates the MyD88/NF-kB pathway and also the MAPK/ERK pathway, leading to release of proinflammatory and chemotactic mediators such as IL-8, CXCL2, TNF-α, and IFN-β. 174,175 Macrophage activation in the presence of antiAcanthamoeba antibody and IFN-γ has been shown to demonstrate trophozoite killing activity. 167,176 Macrophages are thought to be a crucial mediator in early infection: depletion of macrophages in a Chinese hamster model of Acanthamoeba keratitis produced a notable worsening of disease.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…Several groups have shown that TLRs recognize pathogens during ocular infection [26,27] . Recently, others and we have shown that TLR4 is expressed by HCE cells and is responsible for the recognition of Acanthamoeba trophozoites [24,40,41] . In this study, we aimed to determine the components of Acanthamoeba trophozoites that interact with TLR4 on corneal epithelial cells and trigger chemokines production.…”
Section: Discussionmentioning
confidence: 90%
“…Study of AK pathogenesis raises the hope of solving difficulties in targeting therapeutic agents to treat AK; therefore, several studies have been orchestrated on the pathogenesis of AK [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . More recently, we observed that Acanthamoeba trophozoites activate toll-like receptor 4 (TLR4) on human and Chinese hamster corneal epithelial cells in vitro and in vivo and stimulate cytokine secretion and progression of keratitis [24] .…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations